Aportes al conocimiento de la reproducción del Atajacaminos Colorado (Antrostomus rufus) en Argentina - Salvador, Sergio A.; Bodrati, Alejandro; Salvador, Lucio A. (Nuestras Aves, 2014)
Este artículo no cuenta con un resumen.